Effect of seepage on change in stress distribution scenario in static and seismic behaviour of earthen dams - Nandi, N.; Roychowdhury, A.; Dutta, S.C. (Zielona Góra: Uniwersytet Zielonogórski)
The present study makes an effort to understand the damage of earthen dams under static and seismic loading condition. To make the investigation more realistic, behaviour of earthen dams considering the occurrence of a phreatic line indicating the submerged zone due to seepage within the dam body is considered. In case of earthen dams, homogeneous or nonhomogeneous, the consideration of the occurrence of a phreatic line or seepage line through the dam body is an important part of the earthen dam design methodology.
Keywords: complete quadratic combination method; harmonic load; finite element analysis